Associations of Medication Regimen Complexity with COPD Medication Adherence and Control - Federman AD; O'Conor R; Wolf MS; Wisnivesky JP (International Journal of COPD, 2021)
Alex D Federman,1 Rachel O’Conor,2 Michael S Wolf,2 Juan P Wisnivesky1 1Division of General Internal Medicine, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 2Division of General Internal Medicine, Feinberg School of Medicine, Northwestern University, Chicago, IL, USACorrespondence: Alex D FedermanDivision of General Internal Medicine, Icahn School of Medicine at Mount Sinai, 1 Gustave L. Levy Place, New York, NY, 10029, USATel +1 212 824-7565Fax +1 212 824-2317Email alex.federman@mssm.eduIntroduction: Medication adherence is often low among people with chronic obstructive pulmonary disease (COPD) and medication regimen complexity may be a contributing factor. In this study, we sought to examine the role of medication regimen complexity in COPD medication adherence among patients with multimorbidity.Methods: We performed cross-sectional analysis of data on COPD patients in primary care and pulmonary practices in New York City and Chicago (n=400). Regimen complexity was represented by the medication regimen complexity index (MRCI) and simple medication count. Adherence was measured by self-report and inhaler dose counts. Disease control measures included the COPD severity score (COPDSS) and the Medical Research Council (MRC) severity index.Results: Mean age of study participants was 69 years, 66% had MRC grades 4 or 5, and 45% had low medication adherence. MRCI scores did not differ significantly between those with and without adequate medication adherence. Patients with higher MRCI scores were more likely to have severe COPD (OR 5.00, 95% CI 1.46– 17.1, p=0.01) and dyspnea grades 3 or 4 (OR 2.27, 95% CI 1.03– 5.03, p=0.04). Significant associations of medication count with COPD severity were also observed.Discussion: These findings demonstrate that among patients with COPD and comorbid hypertension and diabetes, higher medication regimen complexity is associated with worse COPD control but not with COPD medication adherence.Keywords: chronic obstructive pulmonary disease, multimorbidity, medication regimen complexity, medication adherence